DNAzyme concatemer-catalyzed precipitation on an interdigitated micro-comb electrode for capacitance immunosensing of interleukin-6 with rolling circle amplification. (23rd December 2020) - Zhang, Jianming; Lin, Jia; Zheng, Tingjin; Jiang, Yancheng; Luo, Shimu; Lin, Yao; Zhang, Zhishan
Abstract : A novel capacitance immunosensor based on DNAzyme concatemer-amplified signal-generation tags was developed for the sensitive detection of interleukin-6 (IL-6) on an interdigitated micro-comb electrode. Abstract : A novel capacitance immunosensor based on DNAzyme concatemer-amplified signal-generation tags was developed for the sensitive detection of interleukin-6 (IL-6) on an interdigitated micro-comb electrode. To construct such an immunosensor, monoclonal mouse anti-human IL-6 antibodies were covalently conjugated onto a bovine serum albumin (BSA)-coated electrode using the glutaraldehyde cross-linker. Gold nanoparticles heavily functionalized with primer DNA (for the subsequent rolling cycle amplification; RCA) and polyclonal rabbit anti-human IL-6 antibodies were used for the development of a sandwich-type immunoassay on the modified interdigitated electrode in the presence of the target IL-6. Thereafter, the attached primer DNA with the immunocomplex triggered the RCA reaction for the formation of numerous DNAzyme concatemers with the assistance of hemins and G-rich DNA probes. DNAzyme concatemers catalyzed 4-chloro-1-naphthol into insoluble benzo-4-chlorohexadienone and were deposited onto the electrode, thus resulting in the local capacitance variation of the interdigitated micro-comb electrode. The performance and external factors affecting the analytical properties were studied in detail. Under optimum conditions, the capacitance variations of the immunosensor were proportional to the IL-6 concentration in the dynamic range of 1.0–1000 pg mL −1 at a detection limit of 0.68 pg mL −1 . Good reproducibility, high specificity and acceptable storage stability were acquired for the analysis of the target IL-6. Moreover, the capacitance immunosensor was utilized to determine IL-6 in human serum specimens and gave well-matched analytical results in reference to the human IL-6 ELISA kit.